TECHNOLOGY FOR AUTOMATED CONSTRUCTION OF DOMAIN DICTIONARIES WITH SPECIAL PROCESSING OF SHORT DOCUMENTS - Kungurtsev, O. B.; Mileiko, I. I.; Novikova, N. O. (Radio Electronics, Computer Science, Control, 2024)
Context. The task of automating the construction of domain dictionaries in the process of implementing software projects based on the analysis of documents, taking into account their size and presentation form. Objective. The goal of the work is to improve the quality of the dictionary based on the use of new technology, including special processing of short documents. Method. A model of a short document is proposed, which presents it in the form of three parts: header, content and final. The header and final parts usually contain information not related to the subject area. Therefore, a method for extracting content based on the use of many keywords has been proposed. The size of a short document (its content) does not allow determining the frequency characteristics of words and, therefore, identifying multi-word terms, the share of which reaches 50% of all terms. To make it possible to identify terms in short documents, a method for their clustering is proposed, based on the selection of nouns and the calculation of their frequency characteristics. The resulting clusters are treated as ordinary documents, since their size allows for the selection of multi-word terms. To highlight terms, it is proposed to select sequences of words containing nouns in the text. Analysis of the frequency of repetition of such sequences allows us to identify multi-word terms. To determine the interpretation of terms, a previously developed method of automated search for interpretations in dictionaries was used. Results. Based on the proposed model and methods, software was created to build a domain dictionary and a number of experiments were conducted to confirm the effectiveness of the developed solutions. Conclusions. The experiments carried out confirmed the performance of the proposed software and allow us to recommend it for use in practice for creating dictionaries of the subject area of various information systems. Prospects for further research may include the construction of corporate search systems based on dictionaries of terms and document clustering.